Perdagangan Internasional di Era Digital: Peluang dan Tantangan bagi Negara Berkembang - Ningrum, Eka Milia; Sakuntala, Dwita (Lembaga Yasin AlSys, 2025)
This study aims to analyze the opportunities and challenges of international trade in the digital era for developing countries, particularly Indonesia. A qualitative approach with a descriptive-analytical method was employed to provide an in-depth understanding of the dynamics of digital trade, including the factors influencing its success and obstacles. The research data was collected through a comprehensive literature review of official reports from international organizations such as the WTO, UNCTAD, and the World Bank, as well as related academic publications. The findings indicate that Indonesia faces several challenges in digital trade, including the need for adaptive regulations, cybersecurity issues, digital infrastructure gaps, and human resource development. However, the digital era also presents significant opportunities, such as increased access to international markets through e-commerce platforms, the growth of the fintech sector, and the potential to become a technological innovation hub in Southeast Asia. To optimize these opportunities, investments in education, digital infrastructure, and active participation in international forums are essential. This study concludes that although the challenges of international trade in the digital era are complex, the opportunities it offers can provide substantial benefits for developing countries if effectively managed.